Strategi Keunggulan Bersaing Berdasarkan Metode Porter’s Five Forces pada Ayam Geprek Geprekkin Jl. Gurun Aua Kec. Buanuhampu, Kubang Putiah Kabupaten Agam - Rani Monika; Era Sonita (Lembaga Yasin AlSys, 2026)
Although competitive advantage strategies in culinary businesses have received attention in various studies, studies that specifically discuss the application of Porter’s Five Forces in increasing sales turnover in local culinary microenterprises remain limited. This study aims to analyze competitive advantage strategies based on Porter’s Five Forces in increasing sales turnover at Ayam Geprek Geprekkin Kubang Putiah, Agam Regency. This study employed a qualitative approach with a case study design, involving participants consisting of the business owner, employees, and consumers selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the interactive thematic analysis technique of the Miles and Huberman model. The results showed that the level of business competition was in the high category, with the threat of new entrants, the threat of substitute products, and buyers’ bargaining power as the dominant factors affecting the decline in sales turnover. The strategies that had been implemented, such as menu innovation, variations of sambal, promotion through social media, and the provision of discounts, had not been able to increase sales significantly. These findings contribute to the development of Porter’s Five Forces theory while broadening understanding of the competitive dynamics of microenterprises in the local culinary sector. This study concludes that sustainable product differentiation, improvement in service quality, and more effective marketing strategies are important factors in enhancing business competitiveness. The implications of this study include theoretical contributions to enriching the strategic management literature and practical contributions for business actors in formulating more adaptive business strategies, while also opening opportunities for further research related to internal business factors and the use of digital technology.